Pengaruh Outdoor Education Terhadap Pengembangan Sikap Empati - Muhammad Wildan Firdaus; Yogi Akin; Gano Sumarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effect of outdoor education on the development of empathy among children at Rumah Bintang, as a solution to low social-emotional skills and the prevalence of bullying. A quantitative method was used with a one-group pretest-posttest experimental design involving 32 children aged 10–11 years who were selected through total sampling. The research instrument used the Basic Empathy Scale (BES), analyzed using a paired-sample t-test. The results showed a significant increase in the mean empathy score from 56.22 to 68.47, with a significance level of 0.000 < 0.05. This improvement occurred through the internalization of responsibility in activities such as rock climbing, which compelled the children to genuinely understand others’ perspectives. The study’s conclusion establishes that outdoor education is a strategic pedagogical approach that effectively strengthens students’ emotional intelligence and prosocial behavior; therefore, it is recommended as a model for character education in elementary schools. Keywords: Outdoor Education, Empathy, BES, Elementary School Students. Keywords: Children, BES, Empathy, Outdoor Education